Opportunities for science in touristic shark feeding aggregations – A review - Jan Bierwirth; Thomas Vignaud; Clémentine Séguigne; Eric Clua (Global Ecology and Conservation, 2025)
Shark tourism has been rising exponentially over the past decades. This is particularly true for dive operators that make use of artificial provisioning to attract the animals, increasing the likelihood of encounters for participants. However, this practice is often deemed controversial as previous research has pointed out positive as well as negative consequences of such activities which are often highly case-dependent. In this review, we investigate to which extent these anthropogenic-based activities have contributed to different disciplines within shark related science and discuss its potential future role. We demonstrate its scientific contribution especially in the fields of behavior and social dynamics of large shark species, which are usually elusive and difficult to access in the wild. Additionally, touristic shark feeding sites have benefitted the application and testing of novel methods and technologies. Recent research direction shows that one of the greatest benefits might be the regular access to the same individuals over time, allowing a shift from population-based towards individual-based research. This will advance our understanding of inter- and intra-individual differences and its underlying principles as we will be able to dive deeper into shark personalities, social interactions and their mechanisms.